2022
DOI: 10.1101/2022.12.05.22283089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of Type 1 Diabetes in Children is Not Increased after SARS-CoV-2 Infection: A Nationwide Prospective Study in Denmark

Abstract: Objective It has been hypothesized that SARS-CoV-2 infection in children can increase risk of developing type 1 diabetes. Research Design and Methods We undertook a prospective analysis based on all children in Denmark where we investigated the association between SARS-CoV-2 infection and subsequent risk of type 1 diabetes, using information from several different national Danish registers. Denmark had one of the highest test-rates per capita in the world during the pandemic. Results We did not observe a highe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 8 publications
2
16
1
Order By: Relevance
“…Seven reports from six studies 2,3,5–8 involving 11 220 476 participants (2 140 864 patients with a history of diagnosed SARS‐CoV‐2 infection and 9 079 612 participants in the respective control groups) reported numbers of new‐onset T1DM following SARS‐CoV‐2 infection. Overall, SARS‐CoV‐2 infection was significantly associated with an increase in the risk of new‐onset T1DM in children and adolescents compared with non‐COVID‐19 control groups (RR = 1.42, 95% CI 1.13–1.77, p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven reports from six studies 2,3,5–8 involving 11 220 476 participants (2 140 864 patients with a history of diagnosed SARS‐CoV‐2 infection and 9 079 612 participants in the respective control groups) reported numbers of new‐onset T1DM following SARS‐CoV‐2 infection. Overall, SARS‐CoV‐2 infection was significantly associated with an increase in the risk of new‐onset T1DM in children and adolescents compared with non‐COVID‐19 control groups (RR = 1.42, 95% CI 1.13–1.77, p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…SARS‐CoV‐2 infection was defined by first positive PCR test for SARS‐CoV‐2 in all included studies. The control group in six studies was from non‐COVID‐19 participant 2–4,6–8 and in one study selected from patients with other respiratory tract infections 5 . Studies reported the risk of new‐onset T1DM based on adjustment for age, 3,8 gender, 3,7,8 geographical area and socioeconomic factors, comorbidity, vaccine doses, parental history of T1DM, 7 and calendar time 6,7 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations